2013
DOI: 10.1177/0886109913516454
|View full text |Cite
|
Sign up to set email alerts
|

Healing Through Movement

Abstract: Perceptions of “belly dance” are that it is degrading, exploitive, and incongruous to feminism. Curiously, however, the dance is incredibly popular in various parts of the world, including the United States, as a form of recreation and creative expression. This article examines the apparent disconnect between public perception and practitioner standpoint. Findings indicate a strong holistic healing component, particularly in terms of gendered interpersonal victimization, where belly dance seems to hold potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 14 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Selected studies suggested that DT improves the sensory-motor perceptions of individuals suffering from psychological trauma. Qualitative studies pointed to an improved body awareness and the emergence of a mind–body connection through the sensory experience of movement, rhythm, and relaxation (Fargnoli, 2017 ; Levine & Land, 2016 ; Moe, 2014 ; Özümerzifon et al, 2022 ; Schaeffer & Cornelius-White, 2021 ; Verreault, 2017 ). Also, as demonstrated by an experimental quantitative study using one Flamenco session, the intervention needs to be long enough to produce a change in physical skills, body self-efficacy, or perceived level of fitness (Koch et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Selected studies suggested that DT improves the sensory-motor perceptions of individuals suffering from psychological trauma. Qualitative studies pointed to an improved body awareness and the emergence of a mind–body connection through the sensory experience of movement, rhythm, and relaxation (Fargnoli, 2017 ; Levine & Land, 2016 ; Moe, 2014 ; Özümerzifon et al, 2022 ; Schaeffer & Cornelius-White, 2021 ; Verreault, 2017 ). Also, as demonstrated by an experimental quantitative study using one Flamenco session, the intervention needs to be long enough to produce a change in physical skills, body self-efficacy, or perceived level of fitness (Koch et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…When applied to individuals suffering from psychological trauma, DT is associated with an improvement in the identification, expression, and externalization of emotions. A systematic review (Lee et al, 2022 ) and several qualitative studies particularly identified an improvement in an emotional state, a better recognition of emotions, a better focus on emotions, an improvement in emotional release, and the development of kinesthetic empathy (to feel in one’s own body the movement of the other) (Fargnoli, 2017 ; Ley et al, 2017 ; Moe, 2014 ; Schaeffer & Cornelius-White, 2021 ). A longitudinal cohort study (associated with a RCT studying other dimensions) supported these results, through measurement of the affective valence of 25 women before and after participating in 12 virtual sessions of a creative dance/movement programme ( t (22) = −2.187, p = .04, d = 2.426) (Özümerzifon et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One particular benefit is that leisure activities can positively shape specific aspects of our self-perceptions. For example, women participating in belly dance reported feeling empowered and more comfortable with their bodies as a result of their participation, even despite past physical victimization (Moe 2014). Others who participate in textile crafting as leisure activity have developed their values of sustainability through crafting by becoming more aware of their consumption and waste (Pöllänen 2015).…”
Section: Introductionmentioning
confidence: 99%